SmBa2NbO6 Nanopowders, an Effective Percolation Network Medium for YBCO Superconductors. (21st November 2013) - Vidya, S.; Mathai, K. C.; Rejith, P. P.; Solomon, Sam; Thomas, J. K.
Abstract : The percolation behavior of superconductor-insulator composite, YBa2 Cu3 O7– δ, and nano SmBa2 NbO2 synthesized by modified combustion technique was studied. Particle size of nano SmBa2 NBO6 was determined using transmission electron microscopy. The chemical nonreactivity of nano SmBa2 NbO6 with YBCO is evident from the X-Ray diffraction study which makes it a suitable nanoceramic substrate material for high temperature superconducting films. A systematic increase in the sintered density, approaching the optimum value of the insulating nanophase is clearly observed, as the vol.% of YBCO in the composite decreases. SEM micrograph showed uniform distribution of nanopowder among the large clusters of YBCO. The obtained percolation threshold is ~ 26 vol% of YBCO in the composite. All the composites below the threshold value showed T C ( 0 ) ~ 92  K even though the room resistivity increases with increase in vol.% of nano SmBa2 NbO6 . The values of critical exponents obtained matches well with the theoretically expected ones for an ideal superconductor-insulator system.